Review paperA critical analysis of the ‘amyloid cascade hypothesis’ - A. Armstrong, Richard (Folia Neuropathologica, 2014)
The ‘amyloid cascade hypothesis’ (ACH) is the most influential model of the pathogenesis of Alzheimer’s disease (AD). The hypothesis proposes that the deposition of β-amyloid (Aβ) is the initial pathological event in AD, leading to the formation of extracellular senile plaques (SP), tau-immunoreactive neurofibrillary tangles (NFT), neuronal loss, and ultimately, clinical dementia. Ever since the formulation of the ACH, however, there have been questions regarding whether it completely describes AD pathogenesis. This review critically examines various aspects of the ACH including its origin and development, the role of amyloid precursor protein (APP), whether SP and NFT are related to the development of clinical dementia, whether Aβ and tau are ‘reactive’ proteins, and whether there is a pathogenic relationship between SP and NFT. The results of transgenic experiments and treatments for AD designed on the basis of the ACH are also reviewed. It was concluded: (1) Aβ and tau could be the products rather than the cause of neurodegeneration in AD, (2) it is doubtful whether there is a direct causal link between Aβ and tau, and (3) SP and NFT may not be directly related to the development of dementia, (4) transgenic models involving APP alone do not completely replicate AD pathology, and (5) treatments based on the ACH have been unsuccessful. Hence, a modification of the ACH is proposed which may provide a more complete explanation of the pathogenesis of AD.